Cervical length in spontaneous preterm delivery prediction - Huertas Tacchino, Erasmo (2015)
Objectives: To determine cervical length measured by transvaginal ultrasound between 22 and 24 weeks’ gestation in the prediction of spontaneous preterm birth. Design: Observational analytic cohort type study. Setting: Fetal Medicine Unit, Instituto Nacional Materno Perinatal, Lima, Peru. Participants: Pregnant women with single gestation. Interventions: Cervical length was measured by transvaginal ultrasound in 1 218 pregnant women during routine prenatal care, between 22 to 24 weeks of gestation, in a tertiary hospital center. Main outcome measures: Cervical length measured at 22-24 weeks of gestation and its correlation with spontaneous preterm delivery. Results: The incidence of spontaneous preterm delivery was 11,8%. Cervical  length was normally distributed. Mean (+/- SD) cervical length was 35,1 +/- 8,5 mm (range, 11-72 mm).  Cervical length, history of preterm delivery, multiparity and high social risk were significantly associated with preterm delivery. Spontaneous preterm delivery ( ≤ 37 weeks’ gestation) relative risks for patients with cervical length ≤ 15mm and ≤ 25 mm were respectively 10,9 (IC 95% 8,3-14,2; P ≤ 0,0001) and 9,0 (IC 95% 7,7-10,6; P ≤ 0,0001). For spontaneous preterm delivery a cervical length ≤14,5 mm had positive predictive value of 100%, negative predictive value of 100%, sensitivity of 6,4% and specificity of 97%. Conclusions: A ≤25 mm short cervix as measured by transvaginal ultrasonography between 22 and 24 weeks’ gestation is an important predictor of spontaneous preterm delivery at a third level hospital.